Business, trade and investment relations between China and Brazil - Zhu, Yanghao (2021)
With the establishment of WTO, the development of the world economy has been intensified and the world has become an inseparable whole. China is also taking an active part in international economic cooperation by means of international trade and direct investment. As the largest country in Latin America by area, Brazil and China are both members of the "BRICS" organization, making it a priority country for China to invest abroad. This thesis collects and analyzes the economic conditions and trade-related policies of China and Brazil to understand the intensity of foreign investment of these two countries and their attractiveness to direct investment; Analysis the change of the bilateral trade structure between China and Brazil caused by the trade war between China and the United States; Finally combined with the current situation of trade and investment between China and Brazil, finds out the problems existing in the cooperation and forecasts the prospects of the economic and trade cooperation between these two countries.